CLINICAL CHARACTERISTICS AND OUTCOME OF POSTERIOR CYSTOID MACULAR DEGENERATION IN CHRONIC CENTRAL SEROUS CHORIORETINOPATHY - Mohabati, Danial (Retina, 2020)
PURPOSE: To assess clinical characteristics and visual outcome in chronic central serous chorioretinopathy patients with posterior cystoid retinal degeneration (PCRD). METHODS: Patients' medical records were reviewed retrospectively in 62 cases (83 eyes, mean age = 59 years, 88% male). Data were collected at central serous chorioretinopathy diagnosis, at PCRD manifestation, and at final visit. All treatment modalities were reviewed. Main outcome measures were treatment efficacy in achieving PCRD resolution, and final best-corrected visual acuity. RESULTS: In 63 eyes (76%), subretinal fluid was present at first PCRD manifestation, whereas fluorescein angiography showed active focal or diffuse leakage in 65 eyes (78%). Seventy-six eyes (81%) received treatment, and PCRD had resolved completely in 31 eyes (37%) at the final visit. Photodynamic therapy was most successful in achieving a complete PCRD resolution. Best-corrected visual acuity did not improve, even after complete PCRD resolution (mean baseline best corrected visual acuity = 69 ± 19, and mean final best corrected visual acuity = 67 ± 20 ETDRS letters [20/40 and 20/50 in Snellen equivalent respectively], P = 0.354). CONCLUSION: Posterior cystoid retinal degeneration is a relatively common finding in chronic central serous chorioretinopathy, which is often accompanied by active subretinal fluid leakage. Treatment may be beneficial to stop the subretinal fluid leakage component, but is less likely to result in a complete PCRD resolution and/or a best-corrected visual acuity improvement.